Literature Review: Komitmen Organisasi pada Karyawan Gen Z - Jayanti, Kadek Dwi; Simarmata, Nicholas (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
Generation Z (Gen Z) employees show a significant increase in job turnover rates, with a tendency to change jobs within a short period of time. This tendency is often an indicator of low organizational commitment, as employees who lack emotional attachment and a sense of belonging to the organization are more likely to decide to seek other opportunities. Low organizational commitment is a serious challenge that requires further attention, given the importance of human resource quality that is in line with organizational needs. Therefore, this study aims to identify and map the factors that contribute to organizational commitment among Gen Z employees based on the latest empirical findings. This study uses a literature review method to examine predictors related to organizational commitment among Gen Z employees. The study was conducted descriptively on 10 quantitative articles in the 2020–2025 time frame with a variety of sampling methods and involved respondents from the Gen Z employee group. The results of the study show three main categories of factors that shape organizational commitment among Gen Z employees, namely individual psychological factors, work environment factors, and social and relational factors in the workplace. These findings provide practical contributions for organizations in designing more adaptive and effective human resource management strategies to shape long-term organizational commitment among Gen Z employees.Keywords - Generation Z, Gen Z employee, Literature Review, Organizational Commitment.